Stabilization of sandy subgrade with barley ash and gypsum in a peruvian coastal locality - Zapata Terrones, Frank Antony (2025)
Currently, the roads connecting the human settlements in the district of Nuevo Chimbote, located in the Ancash department, are not paved. The majority of these routes are connected by dirt tracks with a thin layer of coarse aggregate, causing damage to vehicles and making smooth transportation difficult. The conducted research has yielded results that can be beneficial for soil stabilization in sandy areas by adding barley ash and gypsum. Regarding the granulometry analysis, according to the SUCS classification system, the soil is categorized as SP (Poorly graded sands, gravelly sands). As for the AASHTO classification system, it falls under A-3(0), which means it consists of fine sand, without any silt or clay fines. The natural soil without any additives does not exhibit plasticity as it is sandy. The maximum dry density of the natural soil is 1,844 g/cm3, and by adding 3 %, 5 %, and 8 % of cement (CC) along with 10 % of gypsum (Y), the dry densities obtained are 1,766 g/cm3, 1,745 g/cm3, and 1,686 g/cm3, respectively. Concerning the soil’s bearing capacity, the California Bearing Ratio (CBR) at 100 % shows 20,29 % for the natural soil. However, by adding 3 %, 5 %, and 8 % of CC along with 10 % of Y, the CBR values at a penetration of 0.1” are 29,01 %, 42,20 %, and 30,92 %, respectively.